Atlantic meridional heat transports in two ocean reanalyses evaluated against the RAPID array. Issue 2 (31st January 2013) - Haines, Keith; Stepanov, Vladimir N.; Valdivieso, Maria; Zuo, Hao
<x xml:space="preserve">Abstract</x> [1] The Atlantic meridional overturning circulation in two versions of the NEMO <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg371m6x24" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />14</alternatives>° global ocean model has been compared with the RAPID transport array at 26°N. Both model versions reproduce the mean MOC strength well although the Florida Straits flows differ because the pathway of the Gulf Stream is not strongly constrained at this resolution. Both models however have a mean meridional heat transport of 1.07PW, much lower than the 1.35PW from RAPID observations in April 2004–October 2007. Much of the heat transport discrepancy is due to lower transports in summer across the MidOcean (Bahamas‐Africa) section, due to stronger southward geostrophic flows in the top 100 m where the water is warmest. Seasonal thermocline changes increase temperature differences across the basin driving stronger geostrophic shear, but this effect is much weaker in the top 100 m of the RAPID velocity data. The effect accounts for a reduction of 1.1Sv in MOC and 0.1PW in heat transports. The rest of the discrepancy comes from lower Ekman transports from using ERAInterim winds instead of QuikSCAT, a smaller zonally varying "Eddy" heat transport component, estimated from repeat XBT sections in the observations, and the southward throughflow in the model. Other differences in depth structure of the model MOC and RAPID observations are described but have much less impact on heat transports.